Influence of the Alkyl Chain Length on the Self‐Assembly of Amphiphilic Iron Complexes: An Analysis of X‐ray Structures. Issue 21 (7th April 2014) - Schlamp, Stephan; Thoma, Peter; Weber, Birgit
Abstract Several new amphiphilic iron complexes were synthesised and characterised by single crystal X‐ray structure analysis. The Schiff‐base‐like equatorial ligands contain long alkyl chains in their outer periphery with chain lengths of 8, 12, 16 and 22 carbon atoms. As axial ligands methanol, pyridine, 4‐aminopyridine, 4‐(dimethylamino)pyridine and 1, 2‐bis(4‐pyridyl)ethane were used. X‐ray structure analysis of the products reveals different coordination numbers, depending on the combination of equatorial and axial ligand. The driving force for this is the self‐assembly to lipid‐layer‐like arrangements. This can be controlled through the chain lengths and the dimension of the axial ligands in a crystal‐engineering‐like approach. For this an empirical rule is introduced concerning the crystallisation behaviour of the complexes. The efficacy of this rule is confirmed with the crystallisation of an octahedral complex with two docosyl (C22) chains in the outer periphery. The rule is also applied to other ligand systems.